Hubungan Anemia, Tingkat Stres, Aktivitas Fisik, dan Konsumsi Makanan Cepat Saji dengan Kejadian Dismenore Primer Pada Siswi SMA IT Putri Abu Hurairah Mataram - Nirmala, Suci; Novitasari, Novitasari; Rahadianti, Dian; Sudiarta, I Gede (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Dysmenorrhea is severe pain in the lower abdomen during menstruation. Dysmenorrhea is one of the health problems that has a high incidence rate worldwide. The purpose of this study was to determine the relationship between anemia, stress levels, physical activity and fast food consumption with the incidence of primary dysmenorrhea in SMA IT Putri Abu Hurairah Mataram. This research is an observational analytic quantitative research with a cross-sectional study design. The population of this study were all 374 students of SMA IT Putri Abu Hurairah Mataram. The research instruments used were questionnaires in the form of WaLLID score questionnaire, DASS questionnaire, International physical activity questionnaire short form (IFAQ-SF), and Food Frequency Questionnaire (FFQ). Data were analyzed using Spearman, univariate, and bivariate tests. The results showed that (1) there was no significant relationship between anemia and primary dysmenorrhea; (2) there was a significant relationship between stress level and primary dysmenorrhea; (3) there was a significant relationship between physical activity and primary dysmenorrhea; (4) there was a significant relationship between fast food consumption and primary dysmenorrhea.